Penerapan Kurikulum Berbasis Cinta di Mi Al-Islah Palembang: Membangun Pendidikan yang Humanis dan Berkarakter - Syah, Abdurahman; Meiwindah, Meiwindah; Fatihah, M. Restu; Fariza, Zakia Al; Dealova, Jeni (SENTRI: Jurnal Riset Ilmiah, 2025)
This study aims to describe the implementation of the Love-Based Curriculum at Madrasah Ibtidaiyah (MI) Al-Islah Palembang as an effort to build humanistic and character-based education. The Love-Based Curriculum emphasizes values of compassion, empathy, and social responsibility integrated across all subjects. This research uses a qualitative approach with a case study method. Data were collected through in-depth interviews, observations, and documentation, and analyzed using the Miles and Huberman model, including data reduction, display, and conclusion drawing. The results show that the implementation of the Love-Based Curriculum at MI Al-Islah fosters affection, respect for diversity, and collaborative learning. Teachers play a crucial role in creating an empathetic environment and instilling love values in academic and non-academic activities. The curriculum has improved students’ self-confidence, empathy, discipline, and character. Despite challenges such as limited time and class size, collaboration between teachers and parents supports success. Overall, the curriculum effectively integrates intellectual, emotional, spiritual, and social dimensions, making it a transformative Islamic education model.